2020
DOI: 10.5194/hess-24-3835-2020
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the Qaidam mega-lake system under mid-Pliocene climates and its restoration under future climates

Abstract: Abstract. The Qaidam Basin in the north of the Tibetan Plateau has undergone drastic environmental changes during the last millions of years. During the Pliocene, the Qaidam Basin contained a freshwater mega-lake system although the surrounding regions showed increasingly arid climates. With the onset of the Pleistocene glaciations, lakes began to shrink and finally disappeared almost completely. Today, hyperarid climate conditions prevail in the low-altitude parts of the Qaidam Basin. The question of how the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 60 publications
(89 reference statements)
1
11
0
Order By: Relevance
“…However, changes in climate state can alter the TWS and lead to an imbalanced normalΔS (e.g., Jiao et al., 2015; Y. Li et al., 2019; J. Wang et al., 2018). A recent study by Scherer (2020) revealed that under the present climate conditions, the normalΔS in the QB is close to zero, and specific humidity is the main climate driver of the annual normalΔS. He found that the annual normalΔS positively correlates with the annual specific humidity.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, changes in climate state can alter the TWS and lead to an imbalanced normalΔS (e.g., Jiao et al., 2015; Y. Li et al., 2019; J. Wang et al., 2018). A recent study by Scherer (2020) revealed that under the present climate conditions, the normalΔS in the QB is close to zero, and specific humidity is the main climate driver of the annual normalΔS. He found that the annual normalΔS positively correlates with the annual specific humidity.…”
Section: Introductionmentioning
confidence: 95%
“…Wang et al, 2018;. A recent study by Scherer (2020) revealed that under the present climate conditions, the ∆S in the QB is close to zero, and specific humidity is the main climate driver of the annual ∆S. He found that the annual ∆S positively correlates with the annual specific humidity.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another issue is the regional water balance that includes evaporation, precipitation, surface runoff, groundwater storage, and atmospheric humidity influx and loss. Scherer (2020) studied the local climatic driver of net water balance of the Qaidam Basin region in the CA, the mechanism of drying of the Qaidam mega‐lake and its possible restoration under warmer and wetter climate. Wang, Schmidt, et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, detailed temperature reconstructions are lacking for this area. Based on a climate model, Scherer (2020) showed similar mechanisms for the Qaidam Basin, for example, slight changes in water balance allow growth and sustainability of the lakes on longer timescales.…”
Section: Discussionmentioning
confidence: 99%